2022
DOI: 10.1177/15569845221091979
|View full text |Cite
|
Sign up to set email alerts
|

Conversion to Thoracotomy in Non-Small Cell Lung Cancer: Risk Factors and Perioperative Outcomes

Abstract: Objective: We aimed to identify predictors of conversion to thoracotomy and test the hypothesis that conversion is associated with inferior perioperative outcomes in non-small cell lung cancer (NSCLC). Methods: We queried the National Cancer Database for patients with stage I to III NSCLC undergoing minimally invasive surgery (MIS) during 2010 to 2016. We compared clinicopathologic factors between patients undergoing MIS with and without conversion. We fitted multivariable regression models to identify indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…This conclusion is aligned with many previous publications enrolling early-stage or locally advanced NSCLC cases (23,24,39). However, at least four research revealed that fewer patients who received RATS converted to thoracotomy when compared with those undergoing VATS (27,(40)(41)(42).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This conclusion is aligned with many previous publications enrolling early-stage or locally advanced NSCLC cases (23,24,39). However, at least four research revealed that fewer patients who received RATS converted to thoracotomy when compared with those undergoing VATS (27,(40)(41)(42).…”
Section: Discussionsupporting
confidence: 82%
“…This conclusion is aligned with many previous publications enrolling early-stage or locally advanced NSCLC cases ( 23 , 24 , 39 ). However, at least four research revealed that fewer patients who received RATS converted to thoracotomy when compared with those undergoing VATS ( 27 , 40 42 ). Importantly, RATS was also found to reduce conversion incidence for NSCLC patients with neoadjuvant immunochemotherapy than VATS ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a previous study indicating inferior outcomes in NSCLC. 28 Hospital volume in the top 5th percentile decreased mortality risk by 31%, and increased TOO likelihood by 93% as compared to low-volume hospitals. This highlights the role of surgeon competence and experience, as disadvantaged patients may lack access to facilities with NSCLC volume and proper MIS experience.…”
Section: Discussionmentioning
confidence: 89%
“…This finding is consistent with a retrospective National Cancer Database analysis that found neoadjuvant chemotherapy to be associated with a higher conversion rate of 18.3% than those without neoadjuvant treatment with a p < 0.01. In contrast, Muslim et al found neoadjuvant treatment was not an independent predictor of conversion [38]. Comparatively, a meta-analysis of early-stage NSCLC without neoadjuvant treatment found a median conversion rate of 8.1% (range 0-15.7%) [8].…”
Section: Discussionmentioning
confidence: 91%